Modeling the Relationship Between Meaning in Life and Suicidal Tendency with the Mediating Role of Self-Efficacy in Young Adults - Falahi, Roya; Mahmoudi, Armin; Afrazizadeh, Seyed Faizullah (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to investigate the structural relationship between meaning in life and suicidal tendency and to examine the mediating role of self-efficacy in this relationship among young adults living in Tehran.Methods and Materials: The present study employed an applied descriptive-correlational design using structural equation modeling. The statistical population consisted of young adults aged 18 to 35 years residing in Tehran in 2025. A total of 400 participants were selected through cluster random sampling from different municipal districts. Data were collected using the Meaning in Life Questionnaire (MLQ), the Beck Scale for Suicide Ideation (BSSI), and the General Self-Efficacy Scale (GSES). After screening the data for missing values, outliers, normality, linearity, and multicollinearity, the proposed structural model was tested. Model adequacy was evaluated using multiple goodness-of-fit indices, including χ²/df, RMSEA, CFI, NFI, GFI, and AGFI.Findings: The proposed structural model demonstrated acceptable fit to the data (χ²/df = 2.41, RMSEA = .07, CFI = .94, NFI = .92, GFI = .95, AGFI = .94). Meaning in life had a significant negative direct effect on suicidal tendency (β = −.61, z = −6.57, p = .001), indicating that greater perceived meaning was associated with lower suicidal tendency. Self-efficacy also showed a significant negative direct effect on suicidal tendency (β = −.49, z = −4.27, p = .001). Furthermore, the indirect effect of meaning in life on suicidal tendency through self-efficacy was significant (β = −.19, z = −2.60, p = .009), supporting the mediating role of self-efficacy in the model.Conclusion: The findings indicate that meaning in life serves as a significant protective factor against suicidal tendency both directly and indirectly through self-efficacy. Young adults who perceive greater meaning and purpose in life tend to report stronger self-efficacy beliefs and lower suicidal tendency. Therefore, interventions designed to enhance life meaning and self-efficacy may contribute substantially to suicide prevention efforts among young adults.